Investigation of the electrical properties of standard and low-gas-flow ICPs using novel probes for the direct measurements of RF voltage and current in the load coil and the corresponding calculation of the ICP power1. Issue 10 (23rd October 2015) - Voronov, M.; Hoffmann, V.; Birus, D.; Engelhard, C.; Buscher, W.
<x xml:space="preserve">Abstract</x> For the first time RF voltage and current were measured directly at the ICP load coil.